On the theory of the infinite in modern thought - Jourdain, Eleanor F. (Eleanor Frances), 1863-1924; Jourdain, Philip E. B. (Philip Edward Bertrand), 1879-1919 (Salt Lake City, UT : Project Gutenberg, 2024)
"On the Theory of the Infinite in Modern Thought: Two Introductory Studies" by E. F. Jourdain is a scholarly examination of the interplay between mathematics and philosophy, specifically focusing on conceptions of the finite and the infinite. Written in the early 20th century, this book navigates complex philosophical and mathematical ideas and highlights how developments in one field influence the other. The text delves into significant themes such as the historical evolution of these concepts, their implications for metaphysics and ethics, and the relationships between mathematical theory and philosophical inquiry. The book comprises two studies that articulate the relationship between the finite and the infinite from both philosophical and mathematical perspectives. In the first study, Jourdain explores how different historical periods have perceived and understood the ideas of finitude and infinity, tracing their development from ancient Greece through to modern mathematical advancements, including Cantor's work on transfinite numbers. The second study addresses pragmatism and a theory of knowledge, discussing how knowledge evolves through human interaction with the environment and integrating mathematical logic into philosophical thought. Overall, Jourdain presents a nuanced discussion that underscores the need for a philosophical approach informed by mathematical principles, arguing that both fields must collaborate to enrich understanding of reality. (This is an automatically generated summary.)
The problem of the finite and the infinite -- Pragmatism and a theory of knowledge.
Release date is 2024-11-12
Carol Brown, deaurider and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Knowledge, Theory of; Pragmatism; Infinite